Community Perceptions of Marbante Maradat Transactions in the Perspective of Islamic Law - Sawaldi, Sawaldi; Basir, Gusril (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2025)
The Marbante Maradat tradition in West Sumatra, is a unique and meaningful traditional event. Held before the month of Ramadan, this tradition aims to strengthen social relations between communities, preserve customs and culture, and honor ancestors. The process involves slaughtering animals which are then distributed evenly to the entire community. Traditional figures such as ninik mamak and imam khatib play an important role in implementing this tradition. This study uses a qualitative with a case study approach. Data were collected through direct observation and interviews with traditional and community leaders. Data analysis was carried out using descriptive, inductive, and deductive thinking methods to understand the meaning and significance of this tradition in the context of community life. The results of the study show that the Marbante Maradat tradition remains relevant as a valuable cultural heritage and a symbol of community togetherness. This tradition can also be carried out in accordance with Islamic principles that emphasize justice and willingness. Thus, Marbante Maradat is not only a cultural preservation, but also a means to strengthen community and spiritual ties before Ramadan.